Compressive ion acoustic double layer and its transitional properties for a two electron temperature warm, multi-ion plasma - Steffy, S. V.; Ghosh, S. S. (My University, 2018)
The emergence of the compressive ion acoustic double layer has been investigated for a two electron temperature warm, multi-ion plasma by the Sagdeev pseudopotential technique. It shows that the ambient cooler electron concentration plays a deterministic role in initiating the transition process of a compressive ion acoustic solitary wave to its double layer. Incorporating the derivative analysis for the pseudopotential, the transitional phase was further quantified by assigning a critical value for the ambient cooler electron concentration. It has been observed that, beyond that critical value, the width of the solitary wave increases rapidly with the increasing amplitude which coincides with the aforementioned transitional phase, manifesting a change in the internal microphysics of the structure for that region. A comparison with the satellite observation revealed good agreement validating the present model. The model will be useful in interpreting the observed monopolar structures in the auroral acceleration region.
Keywords: Sagdeev pseudopotential technique; Ion acoustic solitary waves; Ion acoustic double layer